Factors influencing the profitability of Vietnamese commercial banks during the 2013-2024 period - Nguyen, Ngan Bich; Vu, Nhi Yen (Edelweiss Applied Science and Technology, 2025)
This study examines the factors influencing the profitability of Vietnamese commercial banks from 2013 to 2024, a period marked by global financial fluctuations, economic downturns, and the COVID-19 pandemic. The research aims to identify key determinants of bank profitability and propose strategic solutions for financial performance enhancement. Using panel data from nine Vietnamese commercial banks, the study employs various econometric techniques, including Pooled OLS, Fixed Effects Model (FEM), Random Effects Model (REM), and Feasible Generalized Least Squares (FGLS), to ensure robust findings. The results indicate that the equity-to-assets ratio (EAR), GDP growth, and bank size positively impact return on assets (ROA), while non-performing loans (NPL), cost-to-income ratio (CIR), and industry concentration (CR4) negatively affect it. For net interest margin (NIM), GDP growth, EAR, loan-to-deposit ratio (LDR), and COVID-19 have a positive influence, whereas CIR exerts a negative effect. The study provides practical recommendations for Vietnamese commercial banks, including enhancing cost efficiency, strengthening credit risk management, expanding asset size, and adapting to macroeconomic fluctuations. While the research offers valuable insights, future studies should consider additional factors such as digital transformation and international governance standards to provide a more comprehensive analysis.